HOW LOGISTICS COST DRIVES SATISFACTION AND CONTINUOUS-USE INTENTION IN E-COMMERCE - Kho, Jeffry Richie; Andajani , Erna; Kusumawardhany, Prita Ayu (Universitas Nahdlatul Ulama Surabaya, 2026)
The rapid growth of e-commerce volume in Indonesia has led consumers to demand logistics service providers that are fast, efficient, and high in quality. This phenomenon creates challenges in logistics cost management, which can influence customer satisfaction and their intention to continue using the service. This study analyses how logistics cost management influences customer satisfaction, which has a long-term impact on customers’ continuous-use intention logistics services in the e-commerce context. This research collected online survey data from 191 active online sellers across various e-commerce platforms in Indonesia and was analysed using the PLS-SEM method with SmartPLS 4 software. The results show that cost has a significant positive effect on service quality, technology usage, transportation time, and product condition. In addition, technology usage, transportation time, and product condition are also found to have a significant positive effect on customer satisfaction. However, service quality does not have a significant effect on customer satisfaction. Furthermore, customer satisfaction has a significant positive effect on continuous-use intention, confirming that customer satisfaction is a key factor in fostering customer loyalty and encouraging repeated use of the same logistics services. These findings highlight the importance of cost efficiency, technological adoption, delivery speed, and optimal product condition in strengthening business competitiveness and customer retention in the e-commerce industry. This study contributes theoretically and extends the academic literature on the importance of cost management in logistics services to maintain business sustainability, particularly in the e-commerce sector.